Analysis of secondary structure and identification of internal repeats in miRNA precursor sequences of Saccharum officinarum, Saccharum sp. and Sorghum bicolor - Sengupta, Subhadipa; Singha, Ashmita; Ganguli, Sayak (Current botany (Humnabad, India), 2025)
MicroRNAs (miRNAs) are the post-transcriptional regulators of gene expression that interact with mRNA in a sequence-specific manner. These interactions are primarily regulated by the secondary structural conformation of miRNAs. In plants, miRNAs have always been a subject to extensive research to see their explicit roles in overall development, cell to cell communications, metabolism, responses to stress and pathogen invasion. Here, we aimed to gain more understanding of the secondary structure of all possible miRNA precursor sequences (pre-miRNAs from which mature miRNAs are produced) for Saccharum and Sorghum, the two closest monocot relatives among the domesticated cultivated crops. Using computational approaches, altogether, 240 different pre-miRNAs were analyzed among which three different structural patterns were observed. The structural motifs primarily consist of stem, internal loop, bulge, and terminal loop. The pre-miRNAs of Saccharum sp. were found to have the most stable secondary structure with -193.05 kcal/mol free energy suggesting their resistance to nuclease in the cell. The Simple Sequence Repeats (SSRs) within the stem region of pre-miRNAs were found to be predominant with many trinucleotides, tetranucleotides and less frequent pentanucleotide repeats. AUG/AUC was the mostly observed trinucleotide in 80 percent of the studied precursors. The occurrence of these repeat sequences at varying level suggests their role in the proper functioning of miRNAs. Likewise, SSRs provide a molecular basis for the structural conformation of pre-miRNAs. All this information is substantially required for identifying miRNA targets and designing additional miRNA-based strategies to increase crop yields and enhance plant resistance to environmental stresses.